2022
DOI: 10.1111/spsr.12543
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Use for Elected Parliamentarians: Evidence from Politicians' Use of Twitter During the Last Two Swiss Legislatures

Abstract: Notwithstanding growing research on how using social media for political campaigning impacts politicians' chances of winning votes, we still have limited knowledge about whether and how the use of social media and online styles of communication affect political success over successive legislatures. We address this deficit by analyzing a panel dataset about the Twitter activity of politicians who have had a parliamentary mandate at least once. We first demonstrate that politicians' interaction with specific onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The style of political communication embraced by candidates in social media and their frequent use appear to be important for electoral purposes. Politicians who use them to react to voters' comments may be more politically successful than those who do not react because they are evaluated more positively by voters (Reveilhac & Morselli, 2022; Utz, 2009). This interactive style of communication helps create a feeling of empathy between the voters and the political candidate that grows closer the more interaction there is between them (Bright et al, 2020).…”
Section: The Impact Of Internet‐based Technologies On Votesmentioning
confidence: 99%
See 2 more Smart Citations
“…The style of political communication embraced by candidates in social media and their frequent use appear to be important for electoral purposes. Politicians who use them to react to voters' comments may be more politically successful than those who do not react because they are evaluated more positively by voters (Reveilhac & Morselli, 2022; Utz, 2009). This interactive style of communication helps create a feeling of empathy between the voters and the political candidate that grows closer the more interaction there is between them (Bright et al, 2020).…”
Section: The Impact Of Internet‐based Technologies On Votesmentioning
confidence: 99%
“…As remarked by Bene (2018, p. 12), ‘these results suggest that the extra votes can be gained from those voters who see the politicians' content mediated by their Facebook friends rather than the followers who engage with the posts’. Reveilhac and Morselli (2022) found that the proportion of replies given to media via Twitter and the proportion of ‘retweeted’ politicians' messages significantly increased politicians' success. Replies to public concerns also increased their political ranking, whereas replies to citizens penalized it during electoral periods.…”
Section: The Impact Of Internet‐based Technologies On Votesmentioning
confidence: 99%
See 1 more Smart Citation